Patterning human kidney organoids with synthetic Wnt-secreting organizers - Connor C. Fausto; Fokion Glykofrydis; Navneet Kumar; Jack Schnell; Reka L. Csipan; Faith De Kuyper; Minnal Kunnan; Brendan Grubbs; Matthew Thornton; Michael Thompson; Enmian Chang; Xuduo Wen; et al. (Science, 2026)
Human stem cell–derived miniature organs, including kidney organoids, reproduce aspects of tissue development but lack reliable spatial patterning. In embryos, spatial organization is often established by developmental organizers that generate morphogenetic fields. However, how such organizing geometry operates in kidney nephrogenesis—and whether it can be reconstructed in vitro—has remained unclear. Using spatial transcriptomics of human kidney development, we found that nascent nephrons establish a collecting duct adjacent-to-distant polarity bordering a WNT11 - WNT9B signaling boundary. Engineered WNT-secreting cellular organizers introduced into kidney organoids restored this organizing geometry, biasing distal nephron differentiation and orienting nephron morphogenesis toward the signal source, which demonstrates that developmental signaling geometry can be reconstructed synthetically to control tissue patterning.